Expectations of parents and students in grades III school in relation to the teacher - Nadachewicz, Katarzyna (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
According to the National Association for the Education of Young Children, the most important characteristic for teachers of early childhood development is enthusiasm and passion for children. Working with young children all day takes huge measures of patience. In this article I will present what qualities recognized teachers, parents and students as the most important.